The Strategies of Architectural Design Resisting Earthquake in Tall Buildings - Hussain, Shaimaa Hameed; Hussain, Maraim Safa (Al-Nahrain Journal for Engineering Sciences, 2017)
The target of architecture is present buildings serve the requirements of the human both of aesthetic , functional and safety to serve the people needs , and design buildings could  resist the exterior envelopes that may effect on their work in perfect way , and one of the big risks of damage on buildings and people is " the earthquake " and with the scientific developments of buildings field specially the designing of tall buildings ,the architect should have strategies for seismic design for tall buildings. And with The need of founding aclear framework of the strategies of architecture design resistant to earthquake, especially in tall buildings .the research aim to found these strategies by the identification of the  main load applied on the tall building structure and the best solution of structure design that serve the resistance of  lateral load , then search for the best of configuration for seismic design. Also  define the " Damping systems in tall buildings " and clarify the main types and the advantages and disadvantages of each one . Finally discuss the design considerations of using damping systems which found in the research samples .